Roasting Officials in Humorous Discourse by Kiki Saputri: A Critical Discourse Analysis - Sari, Inda Permata; Triyono, Sulis (International Journal of Contemporary Studies in Education, 2023)
This research aims to describe critical discourse analysis, identify classifications based content within discourse of Kiki Saputri official roasting, and the use of implicature official roasting within humorous discourse by Kiki Saputri. This research was qualitative descriptive, data in this research were Kiki Saputri speech and roasting video transcription based on the event of Stand Up in Kompas Tv and Lapor Pak in Trans7. Data collection used listening, taking notes and documentation techniques, data validity used triangulation theory and data triangulation, data analysis used referential match method in interactive model and critical discourse analysis as the data analysis. The results showed the use of hak kekuasaan oleh state officials legitimacy, these state officials were more interested in managing political problems than citizen problems and they were more sensitive about party members’ problems than public problems. In this critical discourse, it was obtained that Kiki, as a comedian, also criticized government related to their work that, according to her, poor government was lack of taking care the poor people, also education problems, citizen needs, and related to social gaps in welfare of poor people which had been not met, yet. Context as a comedian who are the representation of poor people to voice out their feeling toward government who has power through entertaining critical humour.